(NaKADEMIK mARAT nURMUHUMEDOW(B. s (NpRYVOK (B[(NKNIGA(B]: /s - (NnURMUHAMEDOW(B, (NmARATs ((NtA[KENT(B:s Baktria press, 2020)
(NkNIGA POSWQ]ENA VIZNENNOMU PUTI AKADEMIKA m(B.(Nk(B. (NnURMUHAMEDOWA(B: (NDETSTWO(B, (N@NOSTX(B, (NZRELYE GODYs
Keywords: (NaWTOBIOGRAFI^ESKIJ ROMANs